The Hampering Effect of Precipitated Carbon on Hot Metal Desulfurization with Magnesium. Issue 11 (20th November 2019) - Schrama, Frank N. H.; Beunder, Elisabeth M.; Visser, Hessel-Jan; Sietsma, Jilt; Boom, Rob; Yang, Yongxiang
Abstract : Carbon may precipitate during the hot metal desulfurization (HMD) process as a result of carbon oversaturation because of temperature decrease. The precipitated carbon flakes form a layer between hot metal and slag. It is postulated that this carbon layer hampers desulfurization with magnesium by preventing MgS particles from reaching the slag phase. At Tata Steel in IJmuiden, the Netherlands, carbon in hot metal is measured in 657 heats after reagent injection. With this data, it can be determined whether the hampering effect of precipitated carbon on MgS flotation has a significant effect on the performance of the industrial HMD process. Plant data show a correlation between the precipitated carbon and the specific magnesium consumption for hot metal with a low initial sulfur concentration (below 225 ppm). This correlation cannot be found for hot metal with a higher initial sulfur concentration (above 275 ppm). Furthermore, a sulfur mass balance is made over the converter process, that shows no effect of carbon precipitation during HMD on resulfurization in the converter. The limited experimental accuracy of the plant data prevents a quantitative description of the hampering effect. The measurements do suggest that the effect is small. Abstract : During hot metal desulfurization, carbon may precipitate and form a layer between the slag and hot metal. This carbon layer hampers desulfurization by blocking the floating MgS particles. Herein, plant data are used to determine the size of this hampering effect.